2016
DOI: 10.1111/nph.14126
|View full text |Cite
|
Sign up to set email alerts
|

Shuttling of (deoxy‐) purine nucleotides between compartments of the diatom Phaeodactylum tricornutum

Abstract: SummaryDiatom plastids show several peculiarities when compared with primary plastids of higher plants or algae. They are surrounded by four membranes and depend on nucleotide uptake because, unlike in plants, nucleotide de novo synthesis exclusively occurs in the cytosol. Previous analyses suggest that two specifically adapted nucleotide transporters (NTTs) facilitate the required passage of nucleotides across the innermost plastid membrane. However, nucleotide transport across the additional plastid membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…One possibility is that the additional NTT genes in diatoms might be required to move ATP across the extra membranes associated with a secondary plastid (Ast et al. 2009; Chu et al. 2017).…”
Section: Characterized Plastid and Parasite Transporters Represent Onmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the additional NTT genes in diatoms might be required to move ATP across the extra membranes associated with a secondary plastid (Ast et al. 2009; Chu et al. 2017).…”
Section: Characterized Plastid and Parasite Transporters Represent Onmentioning
confidence: 99%
“…In addition to the NTT that they share with primary plastids, diatom NTTs appear to have independent bacterial origins. These genes might be involved in energy transfer across the multiple internal membranes of these secondarily photosynthetic eukaryotes, and not all diatom NTTs have in silico detectable N-terminal targeting signals (Ast et al 2009; Chu et al 2017). Our phylogeny allows direct comparison of Diatom NTTs to their close bacterial relatives and so reveals significant elongations at their N-termini.…”
Section: Characterized Plastid and Parasite Transporters Represent Onmentioning
confidence: 99%
“…Green fluorescent protein (GFP) based targeting experiments have so far been conducted with three diatom NTTs: TpNTT1 and PtNTT1 were localized to the innermost plastid envelope [39], TpNTT2 and PtNTT2 are present in the plastid envelope and/or endoplasmic reticulum membranes [39], and PtNTT5 is found in the endoplasmic reticulum, including the cER [42]. In the case of PtNTT5, the targeting depends on the location of the GFP reporter (fused either N-terminal or C-terminal), and Chu et al [42] concluded from a series of truncation and fusion experiments that accessibility of the C-terminus is important for the ER localization of the protein, while the N-terminus may be altered for instance by fusion of GFP. Interestingly, the alignment performed by Major et al [41], nevertheless, shows an N-terminal extension of this protein compared to the conserved NTT domain.…”
Section: Nucleotide Transporters In Diatomsmentioning
confidence: 99%
“…The most recent phylogenetic analyses show that except TpNTT1 and PtNTT1, which cluster with other plant and algal NTTs, the diatom NTTs are deeply divergent, with similar branch lengths to the plant NTTs as to NTTs from intracellular bacteria (Rickettsiales), or intracellular eukaryotic parasites (Microsporidia) [41,42].…”
Section: Nucleotide Transporters In Diatomsmentioning
confidence: 99%
See 1 more Smart Citation